Active brazing filler metal on SiC particle reinforced aluminium matrix composites. (26th May 2015) - Wang, P.; Xu, D. X.; Cheng, D. F.; Li, Q.; Niu, J. T.
<x content-type="archive" xml:space="preserve">Abstract</x> The joints of aluminium matrix composites with high SiC particle content were achieved by vacuum brazing with Al–12Si–1·5Mg–4Ti foil as active filler. The effect of Ni coating and Ti on the wetting behaviour of filler metal on the composite was investigated. Owing to the presence of Ni coating, the wettability of liquid filler metal on the composite was enhanced obviously, and Ti(AlSi)3 intermetallic is in situ strengthening phase in the seam. Sound joints with well appearance were obtained, and the optimised shear strength of the joint reached 109.3 MPa. Capable welding parameters were broadened by the presence of Ni coating and Al–12Si–1.5Mg–4Ti foil as filler for brazing of aluminium matrix composites with high SiC particle content.